From Conflict to Peace: Exploring Forgiveness, Reconciliation, and Nonviolence in Colombia - Daniel R. Martínez-Bernal; Aura A. Cardozo-Rusinque; Adriana De la Peña-Leiva; Yamile Turizo-Palencia; Aldair Morales-Cuadro; Claudia Arenas-Rivera; Daniela Montero; Wendy Medina; Marina B. Martínez-González (RIMCIS)
This study delves into the concepts of forgiveness, reconciliation, and nonviolence through the experiences of victims, social leaders, and academics involved in Colombia's peacebuilding initiatives. Using focus groups, audio/video recordings, and thematic analysis, the research developed comprehensive categories situated within Bronfenbrenner's bioecological framework. The results indicate that the journey towards forgiveness, reconciliation, nonviolence, and peace encompasses a gradient extending from individual subjective experiences to broader sociocultural contexts. These findings underscore the critical importance of addressing structural inequalities and upholding rights, with implications that resonate profoundly within Colombia's ongoing peacebuilding efforts. Victims provided narratives in a deeply personal and communitarian manner, while leaders and academics emphasized the pivotal role of the State in ensuring rights and addressing inequalities to facilitate forgiveness and reconciliation processes. Overall, the study underscores the complex interplay between personal, societal, and governmental factors in Colombia's peacebuilding efforts, offering valuable insights for future research and policy development.